Profil Masyarakat Petani Kopi Di Desa Pematang Donok Kecamatan Kabawetan Kabupaten Kepahiang - Herwan MDK; Yoga Saputra (Universitas Dehasen Bengkulu, 2022)
The purpose of the study was to find out how the profile of the coffee farming community in Pematang Donok Village, Kabawetan District, Kepahiang Regency. The place of this research is in Pematang Donok Village. The time of the research was carried out on December 15, 2021 to January 15, 2022. The type of research used was descriptive qualitative research. The object of this research is 30 people. Data collection techniques are 1) observation, 2) interviews, 3) documentation. The data analysis techniques are 1) data collection, 2) data reduction, 3) data display, 4) conclusion drawing. Based on the results of the analysis and discussion on